Experimental Investigation of Variations in Spark Timing using a Spark‐Ignition Engine with Hydrogen‐Blended Gasoline. Issue 12 (9th November 2015) - Shivaprasad, K. V.; Chitragar, P. R.; Kumar, G. N.
Abstract: This study describes an experiment conducted using an electronically controllable single‐cylinder high‐speed gasoline engine to analyze the performance and emissions characteristics of various hydrogen–gasoline blends. The experiments have been conducted for various engine speeds and spark timings at the wide open throttle position. The experimental results revealed that the engine brake thermal efficiency and brake mean effective pressure first increase and then decrease with the increase engine speed at all spark timings. The minimum amount of brake specific energy consumption was observed for 20 % hydrogen addition in the total fuel blend at 3000 rpm engine speed and 14 °crank angle (CA) before top dead center (BTDC) spark timing. Hydrocarbon and carbon monoxide emissions were reduced with the retardation of spark timings. Nitrogen oxide emissions were continuously increased with the addition of hydrogen in the fuel blend as well as spark timing advance. Abstract : Giving it gas: This study describes experiments conducted using an electronically controllable high‐speed single cylinder gasoline engine to analyze the performance and emissions characteristics with various hydrogen–gasoline blends. The experimental results show that hydrocarbon/carbon monoxide emissions are reduced with the retardation of spark timings, whereas nitrogen oxide emissions continuously increase with the addition of hydrogen in the fuel blend as well as with spark timing advance.